Blockade of the high‐affinity noradrenaline transporter (NET) by the selective 5‐HT reuptake inhibitor escitalopram: an in vivo microdialysis study in mice. (18th December 2012) - Nguyen, Hai T; Guiard, Bruno P; Bacq, Alexandre; David, Denis J; David, Indira; Quesseveur, Gaël; Gautron, Sophie; Sanchez, Connie; Gardier, Alain M
Abstract : BACKGROUND AND PURPOSE Escitalopram, the S(+)‐enantiomer of citalopram is the most selective 5‐HT reuptake inhibitor approved. Although all 5‐HT selective reuptake inhibitors (SSRIs) increase extracellular levels of 5‐HT ([5‐HT]ext ). some also enhance, to a lesser extent, extracellular levels of noradrenaline ([NA]ext ). However, the mechanisms by which SSRIs activate noradrenergic transmission in the brain remain to be determined. EXPERIMENTAL APPROACH This study examined the effects of escitalopram, on both [5‐HT]ext and [NA]ext in the frontal cortex (FCx) of freely moving wild‐type (WT) and mutant mice lacking the 5‐HT transporter (SERT −/− ) by using intracerebral microdialysis. We explored the possibilities that escitalopram enhances [NA]ext, either by a direct mechanism involving the inhibition of the low‐ or high‐affinity noradrenaline transporters, or by an indirect mechanism promoted by [5‐HT]ext elevation. The forced swim test (FST) was used to investigate whether enhancing cortical [5‐HT]ext and/or [NA]ext affected the antidepressant‐like activity of escitalopram. KEY RESULTS In WT mice, a single systemic administration of escitalopram produced a significant increase in cortical [5‐HT]ext and [NA]ext . As expected, escitalopram failed to increase cortical [5‐HT]ext in SERT −/− mice, whereas its neurochemical effects on [NA]ext persisted in these mutants. In WT mice subjected to the FST, escitalopram increased swimming parameters without affecting climbing behaviour. Finally, escitalopram, at relevant concentrations, failed to inhibit cortical noradrenaline and 5‐HT uptake mediated by low‐affinity monoamine transporters. CONCLUSIONS AND IMPLICATIONS These experiments suggest that escitalopram enhances, although moderately, cortical [NA]ext in vivo by a direct mechanism involving the inhibition of the high‐affinity noradrenaline transporter (NET).